Financial Performance Assessment by Du Pont System On A Hotel Company - Andriani, Rini; Premadha, R Yoga; Hidayat, Taufik Tri; Sunardi, Nardi; Sunardi, Nardi (Indonesian Development of Economics and Administration Journal, 2024)
This study aims to determine the financial performance of hotel companies listed on the IDX in 2020 – 2022 and also what causes the decline in sales, total assets, and net profit of companies measured using Du Pont System analysis. Du Pont System itself is a measurement tool of financial performance that includes the ratio of Total Assets Turnover activity and the ratio of Profitability, namely Net Profit Margin to determine the rate of return on assets owned by the company, namely Return On Investment. This research uses data types, namely time series and data sources, namely secondary data. The research method uses qualitative methods with a sample of 5 companies with a period of 3 years. The results show that the financial performance of hotel companies listed on the IDX in 2020 – 2022 can be said to be good, because they see the average value of NPM, MER, and ROE-DP every year always increases. Although the average value of TATO and ROI-DP fluctuates. Thus, hotel companies listed on the IDX for the 2020-2022 period performed well